2002
DOI: 10.1091/mbc.01-11-0539
|View full text |Cite
|
Sign up to set email alerts
|

Centrosome Reorientation in Wound-Edge Cells Is Cell Type Specific

Abstract: The reorientation of the microtubule organizing center during cell migration into a wound in the monolayer was directly observed in living wound-edge cells expressing ␥-tubulin tagged with green fluorescent protein. Our results demonstrate that in CHO cells, the centrosome reorients to a position in front of the nucleus, toward the wound edge, whereas in PtK cells, the centrosome lags behind the nucleus during migration into the wound. In CHO cells, the average rate of centrosome motion was faster than that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
78
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 51 publications
9
78
0
Order By: Relevance
“…For example, the orientation of the Golgi apparatus may be important because this organelle, which also associates with the PV, can provide microtubule nucleation function (11). The importance of centrosome orientation to the leading edge for directed migration has been controversial because it is not observed in some experimental systems (43)(44)(45)(46). Future studies will be directed to the use of the novel system we have described to elucidate further the mechanistic linkage between centrosome orientation and migratory response.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the orientation of the Golgi apparatus may be important because this organelle, which also associates with the PV, can provide microtubule nucleation function (11). The importance of centrosome orientation to the leading edge for directed migration has been controversial because it is not observed in some experimental systems (43)(44)(45)(46). Future studies will be directed to the use of the novel system we have described to elucidate further the mechanistic linkage between centrosome orientation and migratory response.…”
Section: Discussionmentioning
confidence: 99%
“…30 In one model, of fibroblast migration, it has been demonstrated that a signal dependent on the Cdc42 GTPase is required to orient the centrosome to face the direction of migration, while microtubules emanating from the centrosome interact at their plus ends with EB1 and APC, making contact with the cell cortex at sites involving Discs-large (Dlg), and once again specified by the polarity complex (aPKC and other proteins). [31][32][33] At present, it seems likely that the phenomenon of centrosomal contribution to migration is cell type specific, 34 which may reflect the abundance of differing polarization-associated proteins in diverse cell types. It is only now becoming widely appreciated that cells migrate by a variety of different strategies, and that as cancer cells become metastatic, they can serially adapt different strategies: 35,36 hence, the importance of these observations in human disease remains to be established.…”
Section: Roles Of the Centrosomementioning
confidence: 99%
“…It is well established that positioning of the centrosome may determine the direction of cell movement, most probably through the microtubule system. 29,33 Overexpression of Cdc14B has been previously described to result in microtubules bundling and stabilization as well as decreased microtubule nucleation from the centrosome. 22 Thus, it is possible that some of the effects in cell movements may be due to a direct role of Cdc14B on microtubule dynamics.…”
Section: Discussionmentioning
confidence: 99%